PENGARUH PENGEMBANGAN PROFESIONALITAS TERHADAP MOTIVASI BERPRESTASI GURU SMP NEGERI KECAMATAN PADANG UTARA - Widiyastuti, Yuni; Al Kadri, Hanif; Ermita; Susanti, Lusi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the extent of teacher achievement motivation, the extent of teacher professional development, and the influence of professional development on the achievement motivation of state junior secondary school (SMP Negeri) teachers in Kecamatan Padang Utara. Initial observations indicated that teachers tended to remain within a comfortable routine, treated professional-development activities mainly as an administrative obligation, and avoided professional competition, which raised concern about the strength of their achievement motivation. The study used a quantitative approach with a descriptive-correlational design through a survey method. The population consisted of 128 teachers from three state junior secondary schools, and a sample of 102 teachers was determined using the Slovin formula and proportionate stratified random sampling. Data were collected through a Likert-scale questionnaire consisting of 46 valid statement items and analyzed descriptively and inferentially, including normality, linearity, simple linear regression, t-test, and coefficient of determination, using IBM SPSS Statistics 27. The results show that teacher achievement motivation and teacher professional development are both in the high category, with an achievement level of 81.40% and 81.00% respectively. Simple linear regression produced the equation Y = 66.292 + 0.294X, with tcount 3.820 > ttable 1.984 and p < 0.001, indicating that professional development has a positive and significant effect on teachers' achievement motivation, while explaining 12.7% of its variance (R2 = 0.127). These findings suggest that professional development contributes meaningfully to teachers' achievement motivation, although other factors outside the model remain influential and merit further investigation.